Analysis of Marketing Mix and MSME Loan Distribution Strategies at Bank Tabungan Negara - Rifki Salman Alfarizy; Idqan Fahmi; Moch Hadi Santoso (Journal of Consumer Sciences, 2024)
Bank Tabungan Negara (BTN), a state-owned company, is committed to the government to expand access to capital for all MSMEs. Bank BTN MSME, loan distribution performance, is still low and unable to meet the targets set by the government and regulators, so further studies need to be carried out through market research. This research aims to analyze the marketing mix on the decision to use BTN MSME loan products and formulate loan distribution strategies by improving the marketing mix in connection with the low performance of Bank BTN's MSME loan distribution. The sampling technique used convenience sampling involving 100 respondents, who were then analyzed using SEM-PLS and Importance Performance Analysis (IPA) matrix to determine priorities for improving the marketing mix. The results show a significant effect of the marketing mix variables product, price, place, promotion, people, and process on the decision to use a BTN MSME loan, while the physical evidence does not have a significant effect. There are five indicators of marketing mix variables that take in the high-priority quadrant of the IPA Matrix: price suitability, price affordability, processing time, convenience, and online channels. Based on research results, Bank BTN is advised to prioritize improvement strategies on these five variable indicators to increase BTN MSME loan distribution.